Emerging roles for E3 ubiquitin ligases in neural development and disease - Hale, Maya; Bashaw, Greg J. (Frontiers in Cell and Developmental Biology, 2025)
Neurodevelopment is an intricate process with highly regulated, overlapping stages including neuronal differentiation and axon guidance. Aberrations during these and other stages are tied to the etiology of neurodevelopmental disorders like Autism Spectrum Disorder, Angelman Syndrome, and X-linked Intellectual Disability. Ubiquitination is a dynamic and highly reversible post-translational modification conferred by E3 ubiquitin ligases. Recent discoveries have advanced the understanding of how substrate ubiquitination can guide protein localization, drive protein degradation, and alter protein post translational modifications. In this review, we highlight members of the RING and HECT E3 ligase families to discuss their novel roles in the molecular mechanisms regulating neurodevelopment. These findings are both instrumental for informing the future directions of neurodevelopmental research, and in expanding knowledge of intracellular mechanisms of protein trafficking. In addition, a deeper understanding of the molecular mechanisms of E3 ligase function in development promises to offer new insights into the pathogenesis of neurodevelopmental disorders.